Utilization of Customary Law for Resolution of Land and Natural Resource Disputes: A Restorative Approach - Samsidar Samsidar (Journal of Adat Recht, 2026)
This article examines the utilization of customary law in resolving land and natural resource disputes through a restorative justice approach within Indonesia’s plural legal system. Although customary institutions remain actively used by indigenous communities to resolve disputes based on consensus and social harmony, their normative status within the formal legal system remains uncertain. This study identifies three core legal issues: normative ambiguity concerning the legal force of customary dispute resolution, a legal vacuum in the formal recognition of restorative mechanisms outside judicial processes, and conflicts of norms between customary law and positive state law governing land and natural resources.Using a normative juridical method with statute, conceptual, and case approaches, this article analyzes constitutional provisions, land and natural resource regulations, and legal doctrines on restorative justice and legal pluralism. The analysis demonstrates that customary dispute resolution inherently reflects restorative justice principles, including harm repair, communal participation, and restoration of social relations. However, these mechanisms lack formal legal recognition as binding and enforceable outcomes. Judicial and administrative practices tend to prioritize procedural legality and formal documentation, thereby marginalizing customary restorative settlements and perpetuating legal uncertainty for indigenous communities. This article argues that the persistence of land and natural resource disputes reflects structural deficiencies in Indonesia’s legal framework rather than isolated implementation failures. It proposes a prescriptive framework for institutionalizing customary restorative mechanisms through statutory recognition, administrative integration, and pluralistic judicial interpretation to ensure legal certainty, substantive justice, and constitutional compliance